Effects of Using e-Portfolios on EFL Teachers‟ Reflections - Obaid, Yaquob; Sheikh Ahmed, Ismail; Mohin, Mohaida (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the effects of using e-portfolios in enhancing Omani EFL teachers’ reflections. This qualitative study sought to answer the question: How do e-portfolios enhance Omani EFL teachers’ reflections? In order to answer this research question, the researchers used case studies of six Omani EFL teachers who developed their e-portfolios by writing their reflections in their own journals. The participants took four months to complete these journals. In order to explore how deep were the participants’ reflections, each participant’s journal was analyzed and measured based on a certain rubric pertaining to writing reflective journals found in past studies. Finally, semi-structured interviews were used to elicit the participants’ views regarding particular aspects of the project. The obtained data were classified into two major phases: within the first two months and within the last two months of developing e-portfolios. The findings revealed that the use of e-portfolios enabled the participants to develop their journals from being descriptive and narrative in nature into reflective ones. Other benefits of using e-portfolios that the participants had attained were also reported.